Chest wall thickness and depth to vital structures in paediatric patients: implications for prehospital needle decompression of tension pneumothorax - Terboven, Tom; Leonhard, Georg; Wessel, Lucas; Viergutz, Tim; Rudolph, Marcus; Schöler, Michael; Weis, Meike; Haubenreisser, Holger (Scandinavian journal of trauma, resuscitation and emergency medicine, 2019)
Recommendations regarding decompression of tension pneumothorax in small children are scarce and mainly transferred from the adult literature without existing evidence for the paediatric population. This CT-based study evaluates chest wall thickness, width of the intercostal space (ICS) and risk of injury to vital structures by needle decompression in children.
Gesehen am 15.05.2019